Perencanaan Strategis Sistem Informasi Wisata Hutan Pinus Limpakuwus Dengan Menggunakan Metode Ward And Peppard - Puji Pangestu; Resad Setyadi (JURIKOM (Jurnal Riset Komputer), 2022)
Planning Information Systems (IS) and Information Technology (IT) today helps an organization's success in its business. Limpakuwus pine forest nature tourism located in Baturaden Purwokerto is a tourist spot that utilizes technology, namely Electronic Ticketing manually to assist visitors in ordering tickets. Limpakuwus Baturaden pine forest tourism which is owned by the Indonesian State Forestry Public Company (PERUM PERHUTANI), the East BANYUMAS Forest Management Unit (KPH) currently does not use SI/IT optimally or comprehensively. This research has a purpose, namely to make IS/IT planning for the Limpakuwus Baturaden pine forest tourism. The method in this study uses qualitative research methods, qualitative methods are research that emphasizes in-depth understanding of a problem, qualitative research usually tends to be descriptive and uses more in-depth analysis. This research uses a strategic planning analysis of Ward And Peppard information systems, Ward And Peppard analysis is the identification of a technology or computer-based application portfolio to support organizations in implementing business plans and realizing business goals, Ward And Peppard has an input stage consisting of business environment analysis. external and internal business environment analysis. The output stage consists of business strategy, IS/IT management strategy, IT strategy and future application portfolio. The method of collecting data in this study is through interviews or interviews with the manager of the Limpakuwus Pine Forest tourist attraction. The data from this research is descriptive in the form of secondary data. The results of this study are in the form of IS/IT planning documents for Limpakuwus pine forest tourism and recommendations for IS/IT proposals for tourism objects in Baturaden Limpakuwus Pine Forest